Molecular Dynamics Simulation of Aggregates in the Dodecane/span80 System and Their Behaviour in an Electric Field. (23rd November 2015) - Mannoor, Madhusoodanan; Kang, Sangmo; Suh, Yong Kweon
Abstract : Molecular dynamics simulation of self-assembly of surfactant span80 molecules to form reverse micelles in nonpolar liquid dodecane is carried out. Simulations are performed using a united atom model for dodecane and a hybrid model for span80 molecules. Various physical characteristics of reverse micelle are measured, and the same are compared with available experimental results. Presence of charge carriers in the form of solvated ions in the core of reverse micelles is confirmed by the simulation. Movement of reverse micelles under the effect of uniform external electric field is also discussed.